Impact of COVID-19 On the Introduction of Euro in The Republic of Croatia - Berislav BOLFEK; Dario VIŠTICA; Jurica BOSNA (Communications of International Proceedings, 2021)
This paper presents the effects of COVID-19 on the introduction of the euro in the Republic of Croatia, i.e. the effects on the nominal convergence criteria, which are a prerequisite for Croatia’s entry into the monetary union. The analysis covers the period from 2019, before the start of the COVID-19 pandemic, until the mid of 2021 when the corona pandemic is still existent and has a significant impact on the trends in the economy. In fact, the aim of this paper is to collect the data prior to the start of the pandemic and compare them with the data from 2020, as well as the last available data from 2021 for the purpose of observing the changes in the already achieved values of the convergence criteria in this period. As a result, it will be defined where the Republic of Croatia is in terms of the introduction of the euro in relation to the pre-crisis period. The Republic of Croatia has taken the first step towards the introduction of the euro, as it has joined the European exchange rate mechanism ERM II. It is important to maintain macroeconomic stability where structural reforms and fiscal policy will play a key role. The biggest problem could be meeting fiscal criteria. However, there is still uncertainty due to the pandemic, which according to the results of the analysis in 2020 led to a deterioration of fiscal criteria that were beyond the limits of nominal convergence even in the pre-crisis period. Therefore, it is necessary to conduct economic policy in order to meet the criteria of convergence and reduce the vulnerability of the economy.
Keywords: European Monetary Union; Republic of Croatia; convergence criteria; COVID-19